2009
DOI: 10.1016/j.jas.2009.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Comments on Richards et al., Journal of Archaeological Science 35, 2008 “Strontium isotope evidence of Neanderthal mobility at the site of Lakonis, Greece using laser-ablation PIMMS”

Abstract: Abstract.We present an evaluation of the laser ablation Sr isotope data reported by Richards et al.(2008) for a Neanderthal tooth recovered from a site in Greece. Based on an alternative and analytically more robust method of correcting for isobaric interferences present during the analysis the tooth appears to be isotopically homogenous and within uncertainty of the value for modern seawater. If this is the case then contrary to the migration model proposed by Richards et al. (2008) the Neanderthal individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…Third, whereas the size of the CaPO + offset is independent of the volume of sample ablated, it is dependent on the strontium concentration in the apatite; high Sr apatites being less affected than low Sr ones. Consequently, variations in Sr concentrations within an isotopically homogenous tooth could cause variation in the apparent 87 Sr/ 86 Sr ratio (Nowell and Horstwood, 2009). Simonetti et al (2008) showed that a tooth with over 1500 μg/g (ppm) Sr is sufficient to reduce the effect of CaPO + such that 87 Sr/ 86 Sr by LA-MC-ICP-MS is within uncertainty (typical LA uncertainty is 100 to 200 ppm at 2σ) of conventional dissolution methods.…”
Section: Ca 31 P 16 O +mentioning
confidence: 99%
“…Third, whereas the size of the CaPO + offset is independent of the volume of sample ablated, it is dependent on the strontium concentration in the apatite; high Sr apatites being less affected than low Sr ones. Consequently, variations in Sr concentrations within an isotopically homogenous tooth could cause variation in the apparent 87 Sr/ 86 Sr ratio (Nowell and Horstwood, 2009). Simonetti et al (2008) showed that a tooth with over 1500 μg/g (ppm) Sr is sufficient to reduce the effect of CaPO + such that 87 Sr/ 86 Sr by LA-MC-ICP-MS is within uncertainty (typical LA uncertainty is 100 to 200 ppm at 2σ) of conventional dissolution methods.…”
Section: Ca 31 P 16 O +mentioning
confidence: 99%
“…During laser analyses, potential isobaric interferences cannot be chemically removed from the samples prior to analysis as they are when using solution methods. The relatively low concentration of Sr in tooth enamel and dentine, generally about 50-300 ppm in South Africa, coupled with the potential isobaric interferences, causes lower precision and accuracy when using the laser Nowell and Horstwood, 2009;Vroon et al, 2008;Woodhead et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Copeland et al 2008Copeland et al , 2010Horstwood et al 2008;Simonetti et al 2008;Nowell and Horstwood 2009). The most significant issue has been a proposed 40 Ca-31 P-16 O polyatomic isobaric interference that could inflate the mass 87 signal during laser ablation analysis of calcium phosphate materials with relatively low Sr concentrations such as teeth Simonetti et al 2008).…”
Section: Laser Ablation Mc-icp-msmentioning
confidence: 99%